Tax Education and Income Tax Filing Compliance among Small Taxpayers in Mbarara City - Mwesigye, Boaz; Kijjambu, Frederick Nsambu (American Journal of Accounting, 2024)
Purpose: This study aimed at establishing the relationship between tax education and income tax filing compliance among small taxpayers in Mbarara city. The study was driven by the fact that despite Uganda Revenue Authority’s efforts to improve tax compliance, income tax filing compliance is still low among small taxpayers in Uganda in general and Mbarara city in particular. Materials and Methods: A cross-sectional study design was used to collect data from 33,979 small taxpayers in Mbarara city out of which 31,324 were individual taxpayers while 2,655 were non-individual taxpayers. The sample size included 380 respondents out of which 350 were individual taxpayers while 30 were non-individual taxpayers. Systematic random sampling was used to select respondents from each of the six divisions of Mbarara city. Data was analyzed using SPSS version 26.0 where correlation coefficients were generated and presented in a table. Findings: The correlation analysis revealed that tax education was positively and significantly related to taxpayers’ income tax filing compliance (r=.631, p<0.05). Based on the findings, the study concludes that tax education plays a crucial role in improving income tax filing compliance among small taxpayers. Implications to Theory, Practice and Policy: The study recommends a need for the government and tax authorities, in this case, Uganda Revenue Authority to put in place strategies and programs aimed at improving awareness about income tax filing. Some of these strategies include intensifying tax education and outreach services of the mobile tax office ‘Tujenge Bus Services’ to all locations; introducing basic tax education at earlier stages of formal education such that citizens are informed about their future obligations to file income tax returns; translating all information about income tax filing in different local languages and publishing the same in print format for easy understanding. The study contributed significantly to the Theory of Reasoned Action by highlighting the role of education and sensitization in increasing taxpayer awareness about tax and improving voluntary income tax filing compliance. This will help the government to put in place policies that should be implemented by Uganda Revenue Authority to improve income tax filing compliance.
Keywords: Tax Education; Income Tax Filing Compliance; Small Taxpayer